KINERJA PEGAWAI: FAKTOR GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA - Devita Noviyanti; Yulaikah; Didi Wandi (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2024)
The purpose of this research is to analyze the influence of leadership style on employee performance, the influence of the work environment on employee performance, the influence of leadership style and the work environment on employee performance at the Serang City Small and Medium Enterprises Cooperative Department of Industry and Trade, the sample used is 61 respondents using non-probability sampling technique. The research method used is a quantitative method with data collection carried out through questionnaires, observation, interviews, instrument testing, classical assumption testing, and hypothesis testing using multiple linear regression analysis with the help of SPSS v.26.0. The conclusion of the hypothesis test results in this research is that partially leadership style (X1) has no effect on employee performance (Y) with a significance level of 0.508 > 0.05 and an R Square value of 0.208 (20.8%), partially the work environment ( X2) affects employee performance (Y) with a significance level of 0,000 <0.05 and R Square value of 0.593 (59.3%), simultaneously leadership style (X1) and work environment (X2) has a positive and significant effect on performance employee (Y), with a contribution value of 59.6%. while the remaining 44.4% is influenced by other variables that are not included in this research model, including work discipline, work motivation, workload, organization, compensation, etc.